PARCELAMENTO DE NITROGÊNIO EM CULTIVARES DE ALGODÃO PORTADORAS DO CARÁTER CLUSTER - OLIVEIRA, Izadora Araujo; SILVA, Kelly Gabriela Pereira da; SILVA, Ricardo Leonel; SILVA, Rafael Alves; BRAMBILLA, Henry Vinicíus Ribeiro; ZOZ, Tiago (ANAIS DO ENIC, 2022)
-